Market Entry Regulation and International Competition - Thorsten Upmann; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2003)
As a part of their industry or competition policies governments decide whether to allow for free market entry of firms or to regulate market access. We analyze a model where governments (ab)use these policy decisions for strategic reasons in an international setting. Multiple equilibria of this game emerge; and if the cost difference between domestic and foreign firms is significant, all equilibria induce the same allocation, where production exclusively takes place in the cost-efficient country. Moreover, these equilibria are Pareto efficient if this cost difference is substantial. Only if cost differences are insignificant, may production take place in both countries in equilibrium.
Keywords: D43; F12; L11; L51; 330; intergovernmental competition; competition policy; entry regulation; free market entry; international trade